Criteria of truth - Kidder, Kathleen. (Washington, D.C.)
viii, 256 sayfa
Keywords: “Amidst conflicting information and personal experiences, how can someone distinguish between truth and falsehood? Criteria of Truth: Representations of Truth and Falsehood in Hellenistic Poetry tackles this fundamental question through a study of five Hellenistic poems dated to the third and second centuries BCE: Aratus's Phaenomena, Nicander's Theriaca, Callimachus's Aetia, Apollonius of Rhodes's Argonautica, and Lycophron's Alexandra. Situating these poetic works in their intellectual and literary milieu, Kathleen Kidder applies the philosophic concept of the criterion of truth, arguing that each poetic persona represents a different criterion for interrogating truth and falsehood. Moreover, by analyzing the poems' allusions, myths, and poetic language, Kidder demonstrates how this poetry can encapsulate the tensions not only between truth and falsehood, but also between order and chaos, certainty and doubt, clarity and obscurity, seen and unseen, and being and seeming“ --